Flexible Work Culture Transformation in Enhancing Employee Well-Being During the Sustainable Global Digital Era - Komang Meydiana Hutama Putri (Journal of Mandalika Social Science, 2026)
The rapid advancement of digital technologies has accelerated the transformation of flexible work culture, making it an essential strategy for enhancing employee well-being in sustainable organizations. This study aims to analyze how flexible work culture contributes to employee well-being during the sustainable global digital era. The research employs a qualitative library research approach using content analysis to synthesize information from scholarly books, peer-reviewed journals, research reports, and other relevant academic sources. The analysis is guided by the Job Demands–Resources (JD-R) Theory to examine the relationship between organizational flexibility, digital transformation, and employee well-being. The findings indicate that flexible work culture positively influences employee well-being by increasing autonomy, work-life balance, job satisfaction, engagement, and organizational commitment when supported by adequate organizational resources. However, digital transformation may also generate challenges such as technostress, digital fatigue, and blurred work-life boundaries. Therefore, organizations should integrate flexible work culture with supportive leadership, digital capability, and sustainable human resource management to achieve long-term organizational resilience and employee well-being.